EXTRACTION AND CHARACTERIZATION OF POLYPHENOL OXIDASE FROM APRICOT, APPLE, EGGPLANT AND POTATO - Waleed A. Mahmood (Mesopotamia Journal of Agriculture, 2009)
Polyphenol oxidases (PPOs) from the fruits of apricot, apple, eggplant and potato tubers were extracted by homogenization with potassium phosphate buffer followed by precipitation with 1.5 volumes of cold acetone. Some properties of the isolated PPOs were studied. The optimum pH for potato PPO activity was found to be 6.4 while it was 7 for the other fruits PPOs. Optimum temperature of activity was 20oC for apricot and apple PPOs, while it was 22oC for eggplant and potato PPOs. Potato PPO was the most thermostable followed by eggplant, apricot and apple PPOs. The enzymes from the four sources were stable at neutral pH values at room temperature. Their stabilities decreased sharply at pH below 5. Storage of the enzymes solutions at 4 and -18oC at pH 7 for 3 months indicated that potato PPO possessed the highest stability followed by apricot, eggplant and apple PPOs. Km values toward the substrate catechol were 4, 4.16, 1.25 and 2.4 mM for PPOs of apricot, apple, eggplant and potato, respectively.